Significance of liver function test to assess the diagnosis and the severity of acute appendicitis and predicting complications - Ghazi, Dezhwar Yahya (Journal of Neonatal Surgery, 2025)
Background: One of the most common surgical emergencies that happens in the abdomen is the acute appendicitis. According to the research, liver function tests (LFT) may be utilized to predict the severity of appendicitis and serve as a marker for acute appendicitis. Methods: From January to June 2024, 100 cases of acute appendicitis were observed in the emergency room of “Azadi Teaching Hospital,” located in Duhok City, Kurdistan region, Iraq, as part of a single-center, observational, prospective study. The Research Ethics Committee granted ethical permission (Ref. No. 29112023-10-8). Every patient had blood testing, including liver function tests as well as abdominal ultrasonography. Reports on histopathological findings were also examined. Patients with uncomplicated and complicated appendicitis (perforated, gangrenous) were split into two groups. Microsoft Excel 2020 was used to collect and statistically evaluate the data. Results: Among the 100 patients, 54% were male, while 46% were female. Negative appendectomies were found in 2% of cases. Elevated total bilirubin levels were found in 71% of patients with an uncomplicated appendicitis and 89% of those with complicated appendicitis, yielding a significant p-value of 0.0053 and a sensitivity of 62%. Direct bilirubin was elevated in 88% of cases of uncomplicated appendicitis and 96% in complicated cases, with a significant p-value of 0.05 and a sensitivity of 69%. Both alanine transaminase (ALT)and aspartate transaminase (AST) levels were increased in both groups, especially in the complicated group, with AST elevated in 53% of cases and ALT in 35%. Alkaline phosphatase (ALP) levels were raised in 81% of uncomplicated appendicitis and 82% of complicated appendicitis cases, showing a sensitivity of 70.5%. Conclusion: In summary, liver function tests (LFT) can assist in diagnosing, evaluating the severity, and predicting complications of acute appendicitis by showing increases in total bilirubin, direct bilirubin, and alkaline phosphatase.